Metabolomic Analysis Identifies Differences Between Wild and Domesticated Chili Pepper Fruits During Development (Capsicum annuum L.) - Cervantes-Hernández, Felipe; Ochoa-Alejo, Neftalí; Martínez, Octavio; Ordaz-Ortiz, José Juan (Frontiers in Plant Science, 2022)
Capsicum spp. members are a rich source of specialized compounds due to their secondary metabolism. Some metabolic pathways have suffered modifications during the domestication process and improvement of agricultural traits. Here, we compared non-targeted LC–MS profiles from several areas: wild accessions (C. annuum L. var. glabriusculum), domesticated cultivars (C. annuum L.), and the F1 progeny of a domesticated, and a wild accession cross (in both directions) throughout seven stages of fruit development of chili pepper fruits. The main detected differences were in glycerophospholipid metabolism, flavone and flavonol biosynthesis, sphingolipid metabolism, and cutin biosynthesis. The domesticated group exhibited a higher abundance in 12′-apo-β-carotenal, among others capsorubin, and β-tocopherol. Palmitic acid and derivates, terpenoids, and quercitrin were prevalent in the wild accessions. F1 progeny showed a higher abundance of capsaicin, glycol stearate, and soyacerebroside I. This work supports evidence of the side-affectation of trait selection over the metabolism of chili pepper fruit development. Furthermore, it was also observed that there was a possible heterosis effect over the secondary metabolism in the F1 progeny.